2006
DOI: 10.1021/np0581263
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Diterpenes from the Fruiting Body of Antrodia camphorata

Abstract: Three new compounds, 19-hydroxylabda-8(17)-en-16,15-olide (1), 3beta,19-dihydroxylabda-8(17),11E-dien-16,15-olide (2), and 13-epi-3beta,19-dihydroxylabda-8(17),11E-dien-16,15-olide (3), together with four known compounds, 19-hydroxylabda-8(17),13-dien-16,15-olide (4), 14-deoxy-11,12-didehydroandrographolide (5), 14-deoxyandrographolide, and pinusolidic acid, were isolated from the fruiting bodies of Antrodia camphorata. The structures of compounds 1-3 were elucidated by the analysis of their spectroscopic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 21 publications
0
79
0
Order By: Relevance
“…Although the active compounds wait to be further identified, several terpenoids, such as geraniol, farnesol, and geranylgeraniol, have been confirmed to activate PPAR and its target gene expression. 32) Since several sesquiterpenes, steroids, triterpenoids, and diterpenoids have been found in abundance in the fruiting body of T. camphoratus, 33) it is very likely that the extracts of T. camphoratus activated PPAR mediated by its terpenoid constituents or other steroid constituents. However, we also found that the solid-state culture of T. camphoratus had less effect on reducing the serum glucose and triglyceride levels than the wild fruiting bodies of T. camphoratus.…”
Section: Discussionmentioning
confidence: 99%
“…Although the active compounds wait to be further identified, several terpenoids, such as geraniol, farnesol, and geranylgeraniol, have been confirmed to activate PPAR and its target gene expression. 32) Since several sesquiterpenes, steroids, triterpenoids, and diterpenoids have been found in abundance in the fruiting body of T. camphoratus, 33) it is very likely that the extracts of T. camphoratus activated PPAR mediated by its terpenoid constituents or other steroid constituents. However, we also found that the solid-state culture of T. camphoratus had less effect on reducing the serum glucose and triglyceride levels than the wild fruiting bodies of T. camphoratus.…”
Section: Discussionmentioning
confidence: 99%
“…The extractable HWS content was similar in W-CC and SSC-CC, and higher than in LSC-CC. Several triterpenoids were isolated and identified in methanolic (or ethanolic) extracts of W-CC, [25][26][27][28] and Chen et al 8) have reported that HWS and ethanolic extracts in SSC-CC contained triterpenoids that are found in W-CC.…”
Section: Methodsmentioning
confidence: 99%
“…This feature allows its application as a charged chiral selector over a wide pH range [2][3][4][5][6][7][8][9][10][11][12]. Except for the switching between AC1 and AC4, increasing pH from 7 to 9.3 largely unaffected the migration order of the other isolates.…”
Section: Effect Of Buffer Ph and Organic Modifier On Separationmentioning
confidence: 99%
“…It has also been used in the formulation of nutraceuticals and functional foods in Taiwan to enhance the immune system and liver function [1]. To date, this edible fungus exhibits several important biological activities: anticancer [2][3][4][5], antihepatotoxic [6,7], antihypertensive [8], anti-inflammatory [9,10], antioxidant [11], and neuroprotective activities [12]. A. camphorata inhibits lipopolysaccharide/inteferon (LPS/ IFN)-g-induced inflammatory mediator production in macrophages, as well as tumor cell proliferation [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation